2021
DOI: 10.1002/2211-5463.13067
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide (NMN) protects bEnd.3 cells against H2O2‐induced damage via NAMPT and the NF‐κB p65 signalling pathway

Abstract: An increasing number of studies have shown that nicotinamide mononucleotide (NMN) can inhibit not only ageing but also oxidative stress and inflammatory reactions by improving energy metabolism. However, the role of NMN in regulating the anti‐apoptotic, antioxidative stress and inflammatory responses of brain microvascular endothelial cells is still unknown. Therefore, here we studied the effects of NMN on H2O2‐induced oxidative damage of bEnd.3 cells. In this study, we found that NMN could inhibit the NF‐κBp6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Similarly, NMN treatment has reduced the H 2 O 2 -induced increment of ROS and exhibited a trend to restore the H 2 O 2 -induced decrease of CAT activity in bEnd.3 cells. 51 An earlier study has also reported that NMN can protect neuronal cells from oxidative stress via activation of SOD2. 52 Both the gene and protein expressions of claudin-1 indicated that the NMN supplementation may improve the d -gal impaired barrier function.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, NMN treatment has reduced the H 2 O 2 -induced increment of ROS and exhibited a trend to restore the H 2 O 2 -induced decrease of CAT activity in bEnd.3 cells. 51 An earlier study has also reported that NMN can protect neuronal cells from oxidative stress via activation of SOD2. 52 Both the gene and protein expressions of claudin-1 indicated that the NMN supplementation may improve the d -gal impaired barrier function.…”
Section: Discussionmentioning
confidence: 95%
“…The results above indicate that H 2 O 2 negatively affected the cell cycle progression by changing the gene expression pattern in mGCs. Given that NMN protects against oxidative stress and apoptosis of cells [22,23], we then investigated the effects of NMN supplementation on gene expression patterns and cell cycle in H 2 O 2 -cultured mGCs. Accordingly, when compared with group C (control group), group HN (150 µM H 2 O 2 + 500 µM NMN) was clustered separately, and this indicate there was a significant difference between the two groups (Figure 5A).…”
Section: Transcriptome Analysis Of Mgcs Induced By the Co-addition Of...mentioning
confidence: 99%
“…Interestingly, NMN can partially alleviate the aging-induced depletion of female reproductive capacity [22]. Although some studies have demonstrated that NMN supplementation can improve H 2 O 2 -induced abnormalities in other cell models [23], there is no report on the potential effects of NMN on H 2 O 2 -induced oxidative stress in GCs. In this study, the two in vitro GCs models (mouse ovarian granulosa cells (mGCs) and human granulosa cell lines (KGN)) were employed to investigate the effect of NMN supplementation on gene expression patterns, antioxidant capacity, and cell death of both mGCs and KGN that were exposed to H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…BMECs might be particularly sensitive to NAD+ depletion because of their high energetic demands [ 71 ]. That is why replenishment of intracellular NAD+ levels is beneficial in preventing cerebral vascular aging [ 105 ], or in protecting BMECs from hydrogen peroxide-induced apoptosis in vitro [ 106 ].…”
Section: Brief Overview Of Bmec Apoptosis and Microvessel Pruningmentioning
confidence: 99%